Propensity Score Matching: Identifying Opportunities for Future Use in Nursing Studies - Helena Blažun Vošner; Peter Kokol; Jernej Završnik (Nursing Reports)
Background: The frequency of propensity score matching (PSM) use in research is exponentially increasing; however, its use in nursing has not yet been explored and is possibly underused. Methods: Synthetic knowledge synthesis has been used on two corpora of publications from the Web of Science bibliographic database for the following purposes: first, to identify the content of the current nursing PSM studies; second, to identify the content of nursing observational, retrospective, or other quasi-experimental studies; and finally, based on the above analyses, to explore new possibilities for further use of PSM in nursing. Findings: The use of PSM in nursing is very sparse, but the number and content of observational, retrospective, and similar nursing research is increasing and becoming more extensive. Ten prolific themes in observational nursing studies were identified. Based on these studies, several influential studies in which PSM has already been successfully used in comparable healthcare topics have been selected as opportunities for extended PSM use in nursing. Conclusions: As shown in the healthcare disciplines, the extended use of PSM in nursing research might make nursing research more consistent, relevant, internally and externally valid, and consequently more useful in clinical practice and research.